Summing Zeta

Calculus Level 3

n = 2 ( ζ ( n ) 1 ) = ? \large\sum_{n=2}^\infty (\zeta(n)-1)=?


Notation: ζ ( ) \zeta(\cdot) denotes the Riemann zeta function .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Joseph Newton
Jun 25, 2018

n = 2 ( ζ ( n ) 1 ) = n = 2 [ ( 1 + 1 2 n + 1 3 n + 1 4 n + ) 1 ] = n = 2 ( 1 2 n + 1 3 n + 1 4 n + ) = 1 2 2 + 1 3 2 + 1 4 2 + + 1 2 3 + 1 3 3 + 1 4 3 + + 1 2 4 + 1 3 4 + 1 4 4 + Grouping in columns instead of rows: = n = 2 ( 1 n 2 + 1 n 3 + 1 n 4 + ) Using the formula for the sum of an infinite geometric series: = n = 2 ( 1 n 2 1 1 n ) = n = 2 ( 1 n ( n 1 ) ) = lim N n = 2 N ( 1 n 1 1 n ) = lim N ( 1 1 1 2 + 1 2 1 3 + 1 3 1 4 + . . . + 1 N 2 1 N 1 + 1 N 1 1 N ) = lim N ( 1 1 N ) = 1 \begin{aligned}\sum_{n=2}^\infty\left(\zeta(n)-1\right)=&\sum_{n=2}^\infty\left[\left(1+\frac{1}{2^n}+\frac{1}{3^n}+\frac{1}{4^n}+\dots\right)-1\right]\\ =&\sum_{n=2}^\infty\left(\frac{1}{2^n}+\frac{1}{3^n}+\frac{1}{4^n}+\dots\right)\\ =&\quad\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+\dots\\ &+\frac{1}{2^3}+\frac{1}{3^3}+\frac{1}{4^3}+\dots\\ &+\frac{1}{2^4}+\frac{1}{3^4}+\frac{1}{4^4}+\dots\\ &\quad\vdots\qquad\vdots\qquad\vdots\\ &\text{Grouping in columns instead of rows:}\\ =&\sum_{n=2}^\infty\left(\frac{1}{n^2}+\frac{1}{n^3}+\frac{1}{n^4}+\dots\right)\\ &\text{Using the formula for the sum of an infinite geometric series:}\\ =&\sum_{n=2}^\infty\left(\frac{\frac{1}{n^2}}{1-\frac{1}{n}}\right)\\ =&\sum_{n=2}^\infty\left(\frac{1}{n(n-1)}\right)\\ =&\lim_{N\to\infty}\sum_{n=2}^N\left(\frac{1}{n-1}-\frac{1}{n}\right)\\ =&\lim_{N\to\infty}\left(\frac{1}{1}-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{N-2}-\frac{1}{N-1}+\frac{1}{N-1}-\frac{1}{N}\right)\\ =&\lim_{N\to\infty}\left(1-\frac{1}{N}\right)\\ =&1\end{aligned}

Chew-Seong Cheong
Jun 26, 2018

Similar solution with @Joseph Newton 's

S = n = 2 ( ζ ( n ) 1 ) = n = 2 ( k = 1 1 k n 1 ) = n = 2 k = 2 1 k n = k = 2 n = 2 1 k n = k = 2 1 k 2 ( 1 1 1 k ) = k = 2 1 k ( k 1 ) = k = 2 ( 1 k 1 1 k ) = 1 \begin{aligned} S & = \sum_{n=2}^\infty (\zeta (n) - 1) \\ & = \sum_{n=2}^\infty \left(\sum_{\color{#3D99F6}k=1}^\infty \frac 1{k^n} - 1\right) \\ & = \sum_{n=2}^\infty \sum_{\color{#D61F06}k=2}^\infty \frac 1{k^n} \\ & = \sum_{\color{#D61F06}k=2}^\infty \sum_{n=2}^\infty \frac 1{k^n} \\ & = \sum_{k=2}^\infty \frac 1{k^2}\left(\frac 1{1-\frac 1k}\right) \\ & = \sum_{k=2}^\infty \frac 1{k(k-1)} \\ & = \sum_{k=2}^\infty \left(\frac 1{k-1} - \frac 1k\right) \\ & = \boxed{1} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...